Annotated translation of Ta'wil Mukhtalif al-Hadith - Bahari, Che Amnah (IIUM Press, 2009)
This research intends to translate Ibn Qutaybah's Ta'wil Mukhtalif al-Hadith and to provide annotations to his commentaries. This book comprises of 350 pages. Gerard Le Comte has translated this book into French in 1961. It is observed that in this French translation, there are several mistakes and one needs to rectify them. Indeed Ta'wil is a special book for it deals not only with kalam but elaborates hadith and Qur'anic interpretations as well as their contextualization.